Annotated Old Enggano word list derived from Walland’s “Het Eiland Engano” from 1864 - Krauße, D; Rajeg, GPW (University of Oxford's Sustainable Digital Scholarship (SDS), 2024)
Annotated Old Enggano word list derived from Walland's "Het Eiland Engano" from 1864. The table in the original PDF document was extracted and transformed into computationally searchable .csv and .tsv formats. The remarks column from the original PDF was curated into a long- and wide-table format. Abbreviations used as Remarks are as follows: HL means remarks on High Language; LL means remarks on Low Language; OE indicates sound changes involved from Old Enggano into Modern/Contemporary Enggano (ME); ME indicates the Modern/Contemporary Enggano translation; Other remarks. For future updates, see the Releases on the source GitHub repository.